Analysis of Career Adaptability and Happiness at Work in Fresh Graduate Employees - Audry Puji Rahayu; Maharani Tyas Budi Hapsari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Fresh graduates who have just completed their education are believed to have less mature career preparation. Good career adaptability is believed to support readiness to find work. Mature career readiness can help fresh graduates face job demands and career challenges in the world of work so as to bring happiness at work. This study aims to determine the relationship between career adaptability and happiness at work in fresh graduate employees. This research is a quantitative study using cluster sampling technique with a sample of 112 people. Data collection uses two scales, namely the career adaptability scale and the happiness at work scale. The analysis was carried out using the Product Moment correlation test. The results showed that there is a significant positive relationship between career adaptability and happiness at work in fresh graduate employees (r = 0.688, p = 0.001) which means the research hypothesis is accepted. Additional analysis results show that the career concern aspect has a contribution of 26.18%, the career control aspect is 11.67%, the career curiosity aspect is 8.28%, and the career confidence aspect is 12.86%. Fresh graduate yang baru menyelesaikan pendidikannya diyakini memiliki persiapan karir yang kurang matang. Kemampuan career adaptability yang baik diyakini dapat menunjang kesiapan untuk mencari pekerjaan. Kesiapan karir yang matang dapat membantu fresh graduate menghadapi tuntutan pekerjaan serta tantangan karir di dunia kerja sehingga memunculkan kebahagiaan di tempat kerja. Penelitian ini bertujuan untuk mengetahui hubungan career adaptability dan happiness at work pada karyawan fresh graduate. Penelitian ini adalah penelitian kuantitatif menggunakan teknik cluster sampling dengan sampel berjumlah 112 orang. Pengambilan data menggunakan dua skala yaitu skala career adaptability dan skala happiness at work. Analisis dilakukan dengan menggunakan uji korelasi Product Moment. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara career adaptability dan happiness at work pada karyawan fresh graduate (r = 0.688, p = 0.001) yang berarti hipotesis penelitian diterima. Hasil analisis tambahan menunjukkan bahwa aspek career concern memiliki kontribusi sebesar 26,18%, aspek career control 11,67%, aspek career curiosity 8,28%, dan aspek career confidence sebesar 12,86%.